2021
DOI: 10.1038/s41598-021-92224-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigating morphological changes in the brain in relation to etiology and duration of olfactory dysfunction with voxel-based morphometry

Abstract: Olfactory loss (OL) affects up to 20% of the general population and is related to changes in olfaction-related brain regions. This study investigated the effect of etiology and duration of OL on gray matter volume (GMV) of these regions in 257 patients. Voxel-based morphometry was applied to measure GMV in brain regions of interest to test the effects of etiology and duration on regional GMV and the relation between olfactory function and regional GMV. Etiology of OL had a significant effect on GMV in clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…A more extensive study of congenital and acquired (post-infectious, chronic inflammation due to rhinosinusitis, or idiopathic) olfactory loss also demonstrated an association between grey matter volume and olfactory function in the orbitofrontal cortex 17 . It also showed that duration of olfactory loss for those with acquired olfactory dysfunction, ranging from 0 to over 10 years, was related to more pronounced loss of grey matter in the gyrus rectus and orbitofrontal cortex 17 . On the other hand, it has been reported in a longitudinal study that patients with idiopathic olfactory loss had higher grey matter volume after undergoing olfactory training in various brain regions including the orbitofrontal cortex and gyrus rectus 42 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A more extensive study of congenital and acquired (post-infectious, chronic inflammation due to rhinosinusitis, or idiopathic) olfactory loss also demonstrated an association between grey matter volume and olfactory function in the orbitofrontal cortex 17 . It also showed that duration of olfactory loss for those with acquired olfactory dysfunction, ranging from 0 to over 10 years, was related to more pronounced loss of grey matter in the gyrus rectus and orbitofrontal cortex 17 . On the other hand, it has been reported in a longitudinal study that patients with idiopathic olfactory loss had higher grey matter volume after undergoing olfactory training in various brain regions including the orbitofrontal cortex and gyrus rectus 42 .…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study, 100% of the patients in the subacute stage of the disease were displaying signs of gustatory impairment (hypogeusia), and 86% either hyposmia or anosmia 16 . Such loss of sensory olfactory inputs to the brain could lead to a loss of grey matter in olfactory-related brain regions 17 . Olfactory — whether neuronal or supporting — cells concentrated in the olfactory epithelium are also particularly vulnerable to coronavirus invasion, and this seems to be also the case specifically with SARS-CoV-2 15,1820 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These large numbers may allow us to detect subtle, but consistent spatially distributed sites of damage associated with the infection, thus underlining in vivo the possible spreading pathways of the effects of the disease within the brain (whether such effects relate to the invasion of the virus itself 11,18 https:// doi.org/10.21203/rs.3.rs-1139035/v1, inflammatory reactions 3,4 https:// doi.org/10.1101/2021.02. 23.432474, possible anterograde degeneration starting with the olfactory neurons in the nose, or through sensory deprivation 17,26,27 ). The longitudinal aspect of the study aims to help tease apart which of the observed effects between first and second scans are likely related to the infection, rather than due to pre-existing risk factors between the two groups.…”
Section: Articlementioning
confidence: 99%
“…In a recent study, 100% of the patients in the subacute stage of the disease were displaying signs of gustatory impairment (hypogeusia), and 86% either hyposmia or anosmia 16 . Such loss of sensory olfactory inputs to the brain could lead to a loss of grey matter in olfactory-related brain regions 17 . Olfactorywhether neuronal or supporting -cells concentrated in the olfactory epithelium are also particularly vulnerable to coronavirus invasion, and this seems to be also the case specifically with SARS-CoV-2 15,[18][19][20] .…”
mentioning
confidence: 99%